Eye fixation during multiple object attention is based on a representation of discrete spatial foci - Fluharty, Meg (Sci Rep, 2016)
We often look at and attend to several objects at once. How the brain determines where to point our eyes when we do this is poorly understood. Here we devised a novel paradigm to discriminate between different models of spatial selection guiding fixation. In contrast to standard static attentional tasks where the eye remains fixed at a predefined location, observers selected their own preferred fixation position while they tracked static targets that were arranged in specific geometric configurations and which changed identity over time. Fixations were best predicted by a representation of discrete spatial foci, not a polygonal grouping, simple 2-foci division of attention or a circular spotlight. Moreover, attentional performance was incompatible with serial selection. Together with previous studies, our findings are compatible with a view that attentional selection and fixation rely on shared spatial representations and suggest a more nuanced definition of overt vs. covert attention.